If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = 8z + 3 Reorder the terms: 8 = 3 + 8z Solving 8 = 3 + 8z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8z' to each side of the equation. 8 + -8z = 3 + 8z + -8z Combine like terms: 8z + -8z = 0 8 + -8z = 3 + 0 8 + -8z = 3 Add '-8' to each side of the equation. 8 + -8 + -8z = 3 + -8 Combine like terms: 8 + -8 = 0 0 + -8z = 3 + -8 -8z = 3 + -8 Combine like terms: 3 + -8 = -5 -8z = -5 Divide each side by '-8'. z = 0.625 Simplifying z = 0.625
| 2(x)-0+3(0)=6 | | -60+-70= | | 0+0+z=5 | | -18+17+(-12)+(-15)= | | A=1/212h | | 0+y+0=5 | | 7+28+(-4)= | | x+0+0=5 | | 1+(-8)+5= | | 4(0)+z=8 | | 9-3b=-5+4b | | 10x^4y^2=3xy^3 | | 5x+10=13x-10 | | 5m^2-2m+3=0 | | 0-0+z=4 | | 0-y+0=4 | | x-0+0=4 | | 3(8-2)/2=-2 | | 3(0)+2(0)+z=6 | | z^2+2z-8= | | x^2-16=-4x-10 | | 3(0)+2y+0=6 | | 9x-33=-3(x-5) | | 3x+2(0)+0=6 | | 6(2x+2)=12x+12 | | x*3-2/3=3/4 | | 15(x-1)=0 | | 2(x-7)-x=8 | | w/-4=10 | | r+73=-22 | | 0.06(6y-3)+0.02y=0.10y-0.5 | | 3x-2y-3x= |